Comportamiento de cuyes machos reproductores del ceasa mediante la aplicación del etograma - Guerra Riera, Christian David (2023)
The research project aims to evaluate the reproductive behavior of male guinea pigs at different ages, the observation technique and the ethogram was used as an instrument. 15female guinea pigs and 3 male guinea pigs of different ages were used, in the first compartment a 9-month-old male guinea pig, In the second compartment a 6-month-old male guinea pig and in the third compartment a 3-month-old male guinea pig with a video camera in each cage, which records all behavioral events 24 hours a day, 7 days a week for a period of 2 months for the reading of phenomena, At the time of recording, social behavioral attitudes such as leadership, alertness (raising the head), aggressiveness, reproductive behavioral activities such as reaction to reproductive females such as courtship, sniffing genitalia between guinea pigs and mating were observed. These data were taken by each camera 24 hours a day, considering 12 hours during the day and 12 hours at night. The findings confirmed the reproductive behavior that older males exhibit less sexual activity and less aggression. Guinea pigs raise their heads once every second with an average intensity.